2012
DOI: 10.1007/s10841-012-9528-6
|View full text |Cite
|
Sign up to set email alerts
|

Rural avenues as a refuge for feral honey bee population

Abstract: Several honey bee (Apis mellifera) subspecies are in danger of local extinction because their feral population have almost completely disappeared. An important threat to the feral populations of bees is loss of habitat and loss of woodlands. In many places the only habitat suitable for honey bee nesting are rows of trees along roadsides. We studied a feral population of honey bees inhabiting avenues in northern Poland. We inspected 142 km of avenues and found 45 feral colonies. The estimated density of feral p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
63
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 54 publications
(65 citation statements)
references
References 33 publications
2
63
0
Order By: Relevance
“…Our study strongly suggests that paid pollination services should be expanded to ensure adequate pollination. It also highlights the importance of maintaining large, wild habitat patches interspersed in the agricultural landscape, which provide a diversity of floral and nesting resources for honey bees, native bees and native vertebrates (Oleksa et al 2013). …”
Section: Discussionmentioning
confidence: 99%
“…Our study strongly suggests that paid pollination services should be expanded to ensure adequate pollination. It also highlights the importance of maintaining large, wild habitat patches interspersed in the agricultural landscape, which provide a diversity of floral and nesting resources for honey bees, native bees and native vertebrates (Oleksa et al 2013). …”
Section: Discussionmentioning
confidence: 99%
“…In this study, we used honey bees from feral colonies from the area between Gdańsk and Olsztyn (18°36′-21°1′E, 53°14′-54°24′N) in Northern Poland (Oleksa et al 2013a). This region was originally inhabited by the western and northern European dark bee, A. m. mellifera.…”
Section: Samplingmentioning
confidence: 99%
“…One reason for this belief is that many parts of Europe have experienced extensive forest clearing to produce agricultural land, so there remain few old trees with large cavities-the natural nest sites of honeybees (Oleksa et al 2013). Even in forested nature preserves in Europe, where nesting cavities for honeybees must be plentiful, recent studies have shown that the total density of colonies appears to match the density of managed colonies (Moritz et al 2007;Jaffé et al 2009).…”
Section: Introductionmentioning
confidence: 99%